Perceived attributes of e-commerce and the adoption decision: the case of Malaysian SMEs - Hussin, Husnayati; Mohd Nor, Rafidah; Suhaimi, Mohd Adam (Universiti Kebangsaan Malaysia (UKM), 2008)
Research on e-commerce adoption in SMEs has gained considerable attention in the past few years. However, most of them were conducted in developed countries such as USA, UK or Australia. This study attempts to understand ecommerce adoption amongst Malaysian SMEs, applying the persuasion stage of the Diffusion of Innovation Model by Rogers’s. The objective is to determine the relationship between perceived attributes of e-commerce and the adoption decision by SMEs. A survey method was used to collect data whereby questionnaires were mailed to SME owners or managers in the manufacturing sector. The analysis on 107 responses shows that perceived relative advantage, perceived trialability, and perceived observability have significant influence on the willingness to adopt e-commerce.